Connection between Tumor Suppressor BRCA1 and PTEN in Damaged DNA Repair - Minami, Akari; Nakanishi, Atsuko; Ogura, Yasunori; Kitagishi, Yasuko; Matsuda, Satoru (Frontiers in Oncology, 2014)
Genomic instability finally induces cell death or apoptosis. The tumor suppressor PTEN is a dual-specificity phosphatase which has protein phosphatase activity and lipid phosphatase activity that antagonizes PI3K activity. Cells that lack PTEN have constitutively higher levels of PIP3 and activated downstream PI3K/AKT targets. BRCA1, a well-known breast cancer tumor suppressor, is to associate with breast cancer risk and genetic susceptibility. Many studies have demonstrated that PTEN as well as BRCA1 plays a critical role in DNA damage responses. The BRCA1 functionally cooperates with PTEN and might be an essential blockage in development of several tumors. Actually, the PTEN and BRCA1genes are recognized as one of the most frequently deleted and/or mutated in many human cancers. The PI3K/ AKT pathway is constitutively active in BRCA1 defective human cancer cells. Loss or decrease of these PTEN or BRCA1 function, by either mutation or reduced expression, has a role in various tumor developments. This review summarizes recent findings of the function of BRCA1 and PTEN involved in genomic stability and cancer cell signaling.